I assume that the numbers are: 4,4,6,1,5,2,6
If so, then the MAD is 1.43
To find the MAD, you first find the mean of the list. It is 4.
Then find the absolute difference of each number from the mean.
Those values are: 0,0,2,3,1,2,2
Now find the mean of those numbers and you have about: 1.43
Answer:30+15
Step-by-step explanation:
Step-by-step explanation:
Given
Lin walks half a mile at a constant rate i.e. Lin velocity is constant. So, in the graph, it will be a straight line through the origin.
Lin is still for five minutes and after she began sprinting for the slip up to halfway i.e. Lin is accelerating or velocity is increasing for the halfway and later she started walking for the rest of the way.
Answer:
![y= 5](https://tex.z-dn.net/?f=y%3D%205)
Step-by-step explanation:
Given the system of equations:
![x-y=-11](https://tex.z-dn.net/?f=x-y%3D-11)
![y+7=-2x](https://tex.z-dn.net/?f=y%2B7%3D-2x)
In order to find the y coordinate of the solution we must first find the solution to this system of equations. We first start by solving one of the given equations and then substitute the answer of that into the second equation and further solve to get the final answers.
![x=y=-11](https://tex.z-dn.net/?f=x%3Dy%3D-11)
![y+7=-2x](https://tex.z-dn.net/?f=y%2B7%3D-2x)
![y+7=-2x](https://tex.z-dn.net/?f=y%2B7%3D-2x)
![+ -7](https://tex.z-dn.net/?f=%2B%20-7)
![y = -2x - 7](https://tex.z-dn.net/?f=y%20%3D%20-2x%20-%207)
![x - y = -11](https://tex.z-dn.net/?f=x%20-%20y%20%3D%20-11)
![y = -2x-7](https://tex.z-dn.net/?f=y%20%3D%20-2x-7)
![x-(-2x-7)=-11](https://tex.z-dn.net/?f=x-%28-2x-7%29%3D-11)
![x--2x=x+2x=3x](https://tex.z-dn.net/?f=x--2x%3Dx%2B2x%3D3x)
![3x+7=-11](https://tex.z-dn.net/?f=3x%2B7%3D-11)
![-7](https://tex.z-dn.net/?f=-7)
![-11+-7=-18](https://tex.z-dn.net/?f=-11%2B-7%3D-18)
![3x=-18](https://tex.z-dn.net/?f=3x%3D-18)
![\div3](https://tex.z-dn.net/?f=%5Cdiv3)
![-18\div3=-6](https://tex.z-dn.net/?f=-18%5Cdiv3%3D-6)
![x=-6](https://tex.z-dn.net/?f=x%3D-6)
![y=-2x-7](https://tex.z-dn.net/?f=y%3D-2x-7)
![y=(-2)(-6)-7](https://tex.z-dn.net/?f=y%3D%28-2%29%28-6%29-7)
![-2\times-6=12-7=5](https://tex.z-dn.net/?f=-2%5Ctimes-6%3D12-7%3D5)
![y=5](https://tex.z-dn.net/?f=y%3D5)
Hope this helps.
Answer:
Logarithmic
Step-by-step explanation:
For this exmaple, x is the one increasing by a third power for every y
Logarithmic is the opposite of exponential
Exponential is when y is the one increasing by a power for every x.
Therefore this one is logarithmic.